Board structure and supplementary commentary on the primary financial statements. Issue 3 (4th November 2014) - Tauringana, Venancio; Mangena, Musa
Abstract : Purpose: – The purpose of this paper is to investigate the relationship between the extent and focus of supplementary narrative commentary (SNC) on amounts reported in the primary financial statements and board structure variables. Design/methodology/approach: – The study uses the disclosure index methodology to measure the extent of SNC in annual reports of 167 FTSE 250 companies. Ordinary least squares regression analysis is employed to examine the association between the extent and focus of SNC and board structure variables. Findings: – The findings show that the extent of SNC on amounts reported in the primary financial statements is about 30 per cent, suggesting that companies provide commentary on a small number of amounts reported in the financial statements. In terms of focus of SNC, companies provide greater SNC on amounts in the income statement relative to the balance sheet. The regression results indicate that the extent of SNC is negatively associated with board size, and positively associated with audit committee (AC) independence and financial expertise. Focus of SNC is negatively related to AC independence and finance expertise. Originality/value: – The research contributes to both the voluntary disclosure and impression management literature streams. The findings provide evidence of the extent and focus of SNC on amounts in the financial statements. They also demonstrate that board structure variables are related to the extent and focus of SNC on amounts in primary financial statements. These findings have implications for policy makers who have responsibilities for ensuring that users of annual reports receive adequate information to make decisions.